MOTIVASI MASYARAKAT MEMBELI PAKAIAN BEKAS DI PASAR SENAPELAN PEKANBARU - Nisa Ul Karimah; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
In addition to the basic human needs of food and shelter is the clothing. Humans need clothes to protect and shut himself. But along with the development of human life, clothing is also used as a symbol of status, position, or the position of a person who wears it. In Indonesia the development of the type of clothing or commonly referred to as a fashion quite rapidly now. This makes the development of local production outfit with clothing production less competitive overseas. Everyone will be trying to find quality clothing and famous in order to be seen by people in their environment. Not all people can have a famous brand clothes that have since prices are so expensive. But all of that can be overcome by the inclusion of used clothing from abroad with good material, well-known brand and the price is so cheap.The purpose of this study was to determine the motivation that drives someone to buy used clothing and its status. Because not only the lower classes who buy used clothes but even among the various groups that have a high status are also interested in the used clothing. The Yag theory used in this study is a rational choice theory and the concept of motivation. While the method used is qualitative, using accidental sampling technique of collecting data through interviews and observation. The number of respondents in this study were as many as 15 people.Based on the results of the study all respondents are interested in used clothing for cheap prices and good quality. On the other hand it can also save expenses. used clothes buyers in the market Senapelan dominated by people who work as self-employed, with earnings in the range of one million to two million dollars or more. Of the many shoppers an average age of 20-29 years. information about the existence of second-hand clothes in the market is much more Senapelan obtained from friends who had visited before.Keywords: Motivation, Rational Choice, Social Class